Radiosensitization of Allogenic Subcutaneous C6 Glioma Model with Focused Ultrasound-Induced Mild Hyperthermia - Zhiyuan Xu; David Schlesinger; Robert Andrew Drainville; David Moore; Patcharin Pramoonjago; Jason Sheehan; Frederic Padilla (Life, 2024)
The radiosensitization potential of focused ultrasound (FUS)-induced mild hyperthermia was assessed in an allogenic subcutaneous C6 glioma tumor model in rats. Mild hyperthermia at 42 °C was induced in tumors using a single-element 350 kHz FUS transducer. Radiation was delivered with a small animal radiation research platform using a single-beam irradiation technique. The combined treatment involved 20 min of FUS hyperthermia immediately before radiation. Tumor growth changes were observed one week post-treatment. A radiation dose of 2 Gy alone showed limited tumor control (30% reduction). However, when combined with FUS hyperthermia, there was a significant reduction in tumor growth compared to other treatments (tumor volumes: control—1174 ± 554 mm3, FUS-HT—1483 ± 702 mm3, 2 Gy—609 ± 300 mm3, FUS-HT + 2 Gy—259 ± 186 mm3; ANOVA p < 0.00001). Immunohistological analysis suggested increased DNA damage as a short-term mechanism for tumor control in the combined treatment. In conclusion, FUS-induced mild hyperthermia can enhance the effectiveness of radiation in a glioma tumor model, potentially improving the outcome of standard radiation treatments for better tumor control.